Observing the stars. Love in the age of systems - Jakobsen, Kjetil Ansgar (MedieKultur: Journal of media and communication research, 2010)
A number of scholars have demonstrated how the cultural industry involves people in a participatory culture in which users actively construct personal identities. However, the link between a public of mass-mediated entertainment and the private sphere of intimacy and personal identity is a paradox. A consistent theory to clarify that paradox is lacking in the cultural studies literature. I suggest that social systems theory in the Luhmannian tradition may explain in economical terms why the continuous performance and intensification of the paradox of mass-mediated intimacy is a major trait of contemporary culture. Nevertheless, the article does not address normative issues. It is neither an apology for the culture industry, nor a condemnation. The aim is simply to bring one of the most powerful tools of analysis in social theory today to bear on an aspect of modern society which is as important as it is baffling.